2021
DOI: 10.1371/journal.pone.0261955
|View full text |Cite
|
Sign up to set email alerts
|

Patient and retina specialists’ preferences in neovascular age-related macular degeneration treatment. A discrete choice experiment

Abstract: Introduction and objective Neovascular age-related macular degeneration (nAMD) leads to severe and permanent visual impairment, significantly impacting patients’ quality of life and functional independence. Although treatment with anti- vascular endothelial growth factor (VEGF) prevents and, in some cases, reverses visual damage, the need for frequent monitoring visits and intravitreal injections represents a significant burden on patients, caregivers and retina specialists. Objective To elicit preferences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The decision-making process of patients with AMD is affected by many factors. Marion's and Mueller et al's [9][10][11] studies found that visual improvement, on-demand and less frequent injection programmes, inclusion of health insurance, side effects, respect for patients, provision of information to patients and encouragement of their participation in treatment decisions affect the participation of patients with AMD in treatment decisions to varying degrees at the medical staff level. Mueller et al [12] found that at the patient level, waiting time, treatment plan, treatment effect, and whether the condition worsened affect their participation in treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making process of patients with AMD is affected by many factors. Marion's and Mueller et al's [9][10][11] studies found that visual improvement, on-demand and less frequent injection programmes, inclusion of health insurance, side effects, respect for patients, provision of information to patients and encouragement of their participation in treatment decisions affect the participation of patients with AMD in treatment decisions to varying degrees at the medical staff level. Mueller et al [12] found that at the patient level, waiting time, treatment plan, treatment effect, and whether the condition worsened affect their participation in treatment decisions.…”
Section: Introductionmentioning
confidence: 99%